Risk Factors and Consequences of Food Neophobia and Pickiness in Children and Adolescents: A Systematic Review - Carmen del Campo; Cristina Bouzas; Josep A. Tur (Foods)
Food neophobia and pickiness are the resistance or refusal to eat and/or avoid trying new foods due to a strong reaction of fear towards the food or an entire group of foods. This systematic review aims to assess evidence on the risk factors and effects of food neophobia and picky eating in children and adolescents, giving elements to avoid the lack of some foods that can cause nutritional deficiencies, leading to future pathologies when they are adults. A systematic literature search was performed in Medlars Online International Literature (MEDLINE) via Pubmed and EBSCOhost, LILACS and IBECS via Virtual Health Library (VHL), Scopus, and Google Scholar. MeSH terms used were: ((food neophobia [Title/Abstract]) OR (picky eating [Title/Abstract]) OR (food selectivity [Title/Abstract])) NOT ((anorexia nervosa [MeSH Terms]) OR (bariatric surgery [MeSH Terms]) OR (avoidant restrictive food intake disorder [MeSH Terms]) OR (autism spectrum disorder [MeSH Terms])). One hundred and forty-two (n = 142) articles were selected for children and adolescents (0–18 years old). They were structured according to contents: prevalence, risk factors, consequences, strategies and treatment. The studies showed a prevalence of the need for intervention on modifiable risk factors. Food neophobia and pickiness developed in childhood are conditioned by risk factors related to biological, social, and environmental characteristics, as well as family education and skills. Strategies to minimize or avoid these disorders should be aimed at implementing healthy habits at these levels.